2020
DOI: 10.1177/2042018820969019
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-deprivation therapy and SARS-Cov-2 infection: the potential double-face role of testosterone

Abstract: We read with great interest the recent articles published in Therapeutic Advances in Endocrinology and Metabolism on the role of androgen-deprivation therapy (ADT) in patients with prostate cancer (PC) and SARS-Cov-2 infection. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In the early phase, the immunosuppressive action of testosterone could explain males' greater susceptibility to infection when compared to women in all age groups. When the infection has settled, in elderly males who frequently develop a severe course, lower testosterone levels related to age could result in a lower immunosuppressive effect on the cytokine storm [8]. Given the prior evidence on the role of testosterone in the clinical course of the COVID-19 disease, in this study, we hypothesized and confirmed that testosterone could also be important in the duration of viral positivity.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In the early phase, the immunosuppressive action of testosterone could explain males' greater susceptibility to infection when compared to women in all age groups. When the infection has settled, in elderly males who frequently develop a severe course, lower testosterone levels related to age could result in a lower immunosuppressive effect on the cytokine storm [8]. Given the prior evidence on the role of testosterone in the clinical course of the COVID-19 disease, in this study, we hypothesized and confirmed that testosterone could also be important in the duration of viral positivity.…”
Section: Discussionsupporting
confidence: 55%
“…Previous experiences showed that low testosterone levels were independently associated with worse overall men's health and clinical COVID-19 phenotype, need for intensive care unit (ICU) treatment, and mortality [10,11,[30][31][32][33][34][35]. Moreover, an inverse correlation was found between testosterone levels and IL-6 levels [11], suggesting that testosterone could play an important role in both early and late stages of disease [8]. On the basis of these results, it has been hypothesized that testosterone may play a double-edged role in the pathogenesis of the COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual hormones can be used for therapeutic purposes [ 34 , 35 ]. Quite interestingly, and in line with our results, Seeland et al reported that: “their retrospective study of hormone therapy in female COVID-19 patients shows that the fatality risk for women > 50 years receiving estradiol therapy (user group) is reduced by more than 50%; the OR was 0.33, 95% CI (0.18, 0.62) and the hazard ratio (HR) was 0.29, 95% CI (0.11,0.76).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there is conflicting data on the role of testosterone, its measurement, supplementation, and possible augmentation in COVID-19. While there has been some evidence to suggest a possible positive effect of androgendeprivation therapy (ADT) in prostate cancer patients infected by SARS-CoV2, this has recently been called into question [2]. Conversely, there is mounting evidence that low testosterone levels might actually worsen overall outcome-hypogonadism appears to be a risk factor for a more severe clinical course in COVID-19 [3].…”
mentioning
confidence: 99%